2005
DOI: 10.1007/s00024-005-2670-2
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Stress/Strain and the b-values of Acoustic Emissions at the Underground Research Laboratory, Canada

Abstract: The correlation between the b-values of acoustic emissions (AEs) and the phase of the moon was investigated at the Underground Research Laboratory (URL) in Canada. The same data as those used in IWATA (2002) were examined, which showed that the occurrence of AEs is correlated with the phase of the moon. It was expected, therefore, that the b-value of the AEs would also be sensitive to tidal stress/ strain fluctuations. We investigated the variation of the b-values as a function of the phase of the moon. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The same explanation could apply to our observations since laboratory experiments previously showed that b value variations depend on stress normalized to the maximum failure strength [Scholz, 1968]. Our observed greater sensitivity is also consistent with observation of the b value of acoustic emissions in the laboratory varying with tidal stress [Iwata and Young, 2005].…”
Section: Resultssupporting
confidence: 92%
“…The same explanation could apply to our observations since laboratory experiments previously showed that b value variations depend on stress normalized to the maximum failure strength [Scholz, 1968]. Our observed greater sensitivity is also consistent with observation of the b value of acoustic emissions in the laboratory varying with tidal stress [Iwata and Young, 2005].…”
Section: Resultssupporting
confidence: 92%
“…Because the b-value (or β) may have a temporal and/or regional (lateral and vertical) variation (e.g. Ogata & Katsura 1993;Mori & Abercrombie 1997;Schorlemmer et al 2004;Iwata & Young 2005), one might doubt the validity of our statistical model where we incorporate the GR law with a single b-value. However, the influence of such variations is not noticeable in Fig.…”
Section: O D E L L I N G T H E D E T E C T I O N C a Pa B I L I T Ymentioning
confidence: 99%
“…For example, Hartzell & Heaton (1989) searched for a fortnightly tidal periodicity in the Southern California and global earthquake catalogue, however, no such periodicity was observed. On the other hand, Iwata (2002) and Iwata & Young (2005) demonstrated that fluctuations of tidal stresses at times of full/new moon correlate with increased activity of acoustic emissions. The b-values of acoustic emissions were found to be significantly higher just after the times of full/new moon suggesting that b-values become larger during periods of high stresses.…”
Section: Introductionmentioning
confidence: 99%